SHANGHAI COOPERATION ORGANISATION AND AFGHANISTAN: INTERESTS AND LIMITATIONS (Margalla Papers, 2023)
Shanghai Cooperation Organisation has greater relevance in Afghanistan because of its strategic importance and geographic proximity. For years, the country has harboured numerous extremist groups and insurgents. It has remained a battleground for US-led coalition forces and the Taliban for about two decades. Despite efforts by the US and its allies, peace has yet to be restored in Afghanistan, and the responsibility now rests on regional countries. It is crucial for these states, especially Eurasian nations, to work together to stabilise the war-torn country and bring lasting peace to the region. Therefore, the study examines the push and pull factors of the Shanghai Cooperation Organisation’s interests in Afghanistan and the challenges that come with implementing their peace plans. The data has been collected from various primary and secondary sources, including websites, newspapers and research articles. The paper also highlights two major concerns for the Shanghai Cooperation Organisation, the economic crisis in Afghanistan and the international recognition of the Taliban government. Bibliography EntryKhan, Hameed Ullah, Muhammad Farooq Shah and Muhammad Ilyas Khan. 2023. "Shanghai Cooperation Organisation and Afghanistan: Interests and Limitations." Margalla Papers 27 (1): 82-95.